Propagation of perturbations in an acoustic ferromagnetic medium - Selezov, I.T. (Reports of the National Academy of Sciences of Ukraine, 2019)
A generalization of the equations for the propagation of wave perturbations in the acoustic ferromagnetic medium with a finite speed are presented, as a development of researches in the region of acoustics. Unlike the traditional equations of ferrohydrodynamics, the generalized equations involve the finiteness of a speed of propagating waves, that influences the warming-up of widely used ferrohermetics, especially in the initial stage. The developed generalized equations include, as particular cases, the known continual equations taking the effect of a magnetic field into account. These equations can be useful in applications.